Evidence of s-wave superconductivity in ternary intermetallic La3Pd4Si4. (11th August 2015) - Taylor, S V; Landaeta, J F; Subero, D; Machado, P; Bauer, E; Bonalde, I
Abstract: We measured the temperature dependence of the magnetic penetration depth of La3 Pd4 Si4 down to . We observe a temperature-independent behaviour below, which is firm evidence for a nodeless superconducting gap in this material. The data display a very small anomaly around 1 K which we attribute to the possible presence of a superconducting impurity phase. The superfluid density is well described by a two-phase model, considering La3 Pd4 Si4 and the impurity phase. The present analysis suggests that the superconducting energy gap of La3 Pd4 Si4 is isotropic, as expected for conventional BCS superconductors.